Free Carrier Generation in Organic Photovoltaic Bulk Heterojunctions of Conjugated Polymers with Molecular Acceptors: Planar versus Spherical Acceptors. Issue 8 (5th March 2014) - Nardes, Alexandre M.; Ferguson, Andrew J.; Wolfer, Pascal; Gui, Kurt; Burn, Paul L.; Meredith, Paul; Kopidakis, Nikos
Abstract A comparative study of the photophysical performance of the prototypical fullerene derivative PC61BM with a planar small‐molecule acceptor in an organic photovoltaic device is presented. The small‐molecule planar acceptor is 2‐[{7‐(9, 9‐di‐n‐propyl‐9H‐fluoren‐2‐yl)benzo[c][1, 2, 5]thiadiazol‐4‐yl}methylene]malononitrile, termed K12. We discuss photoinduced free charge‐carrier generation and transport in blends of PC61BM or K12 with poly(3‐n‐hexylthiophene) (P3HT), surveying literature results for P3HT:PC61BM and presenting new results on P3HT:K12. For both systems we also review previous work on film structure and correlate the structural and photophysical results. In both cases, a disordered mixed phase is formed between P3HT and the acceptor, although the photophysical properties of this mixed phase differ markedly for PC61BM and K12. In the case of PC61BM the mixed phase acts as a free carrier generation region that can efficiently shuttle carriers to the pure polymer and fullerene domains. As a result, the vast majority of excitons quenched in P3HT:PC61BM blends yield free carriers detected by the contactless time‐resolved microwave conductivity (TRMC) method. In contrast, approximately 85 % of the excitons quenched in P3HT:K12 do not result in free carriers over the nanosecond timescale of the TRMC experiment. We attribute this to poor electron‐transport properties in the mixed P3HT:K12 phase. We propose that the observed differences can be traced to the respective shapes of PC61BM and K12: the three‐dimensional nature of the fullerene cage facilitates coupling between PC61BM molecules irrespective of their relative orientation, whereas for K12 strong electronic coupling is only expected for molecules oriented with their π systems parallel to each other. Comparison between the eutectic compositions of the P3HT:PC61BM and P3HT:K12 shows that the former contains enough fullerene to form a percolation pathway for electrons, whereas the latter contains a sub‐percolating volume fraction of the planar acceptor. Furthermore, the planar K12 co‐assembles with P3HT into a disordered, glassy phase that partly accounts for the poor electron‐transport properties, and may also enhance recombination due to the strong intermolecular interactions between the donor and the acceptor. The implication for the performance of organic photovoltaic devices with the two acceptors is also discussed.